2013 IEEE 26th International Conference on Micro Electro Mechanical Systems (MEMS) 2013
DOI: 10.1109/memsys.2013.6474269
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strengthening of silicon torsion bar of MEMS scanning mirror by hydrogen anneal

Abstract: This paper reports on the strengthening effect of hydrogen anneal on torsional fracture strength of single crystal silicon (SCS). Moving-magnet-type MEMS mirrors were prepared by fabricating SCS and silicon on insulator (SOI) wafers via deep reactive ion etching (DRIE) as fracture test specimens. As a result of the fracture test of the torsion bar on the mirrors, the torsion bar fabricated using a SCS wafer could be strengthened to about 4 times in average by hydrogen anneal. By contrast, that using a SOI wafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Recent literature has shown that the presence of surface scallops severely limits the fracture strength of SCS [19]. This implies that such surface defects may severely limit the fatigue lifetime of a SCS device, and that complete surface smoothing with hydrogen annealing, such as from 'epi-seal' encapsulation, leads to a fatigue-free device.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has shown that the presence of surface scallops severely limits the fracture strength of SCS [19]. This implies that such surface defects may severely limit the fatigue lifetime of a SCS device, and that complete surface smoothing with hydrogen annealing, such as from 'epi-seal' encapsulation, leads to a fatigue-free device.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…sidewall 'scallops') as another possible surface-defect-based fatigue mechanism. The presence of such scallops severely limits the mechanical strength of SCS [19]. Furthermore, it has been shown that the crack length needed to initiate fracture could indeed be comparable to the surface features caused by scallops, leading to another possible fatigue mechanism [20].…”
mentioning
confidence: 99%
“…Surface modification processes have been attempted to improve the fracture properties of SCS structures by annealing in a hydrogen environment 47,48 or by transient laser annealing 49 . However, careful comparison should be made because such annealing induces changes in material conditions such as the DRIE process alteration, not just in the surface morphology.…”
Section: Comparison With Previous Specimensmentioning
confidence: 99%
“…These observations suggest that the surface scallops formed by DRIE cannot be regarded directly as an initial crack for brittle fracture. Including other experimental results 48,51 exhibiting the improvement effects of surface treatments, further detailed comparisons will be required. Because the strength evaluation methods (fracture or fatigue) give only phenomenological results, additional assistance from microscopic technologies will be strongly desired to further elucidate the surface condition effects.…”
Section: Comparison With Previous Specimensmentioning
confidence: 99%
“…There are various methods to improve the surface roughness and strength of silicon microstructures, such as anisotropic wet etching of silicon [4], hydrogen annealing [5], oxidation [6], and laser ablation [7]. Among them, smoothing using oxidation is simple and easy to implement to standard fabrication process.…”
Section: Introductionmentioning
confidence: 99%